Do green funds contribute to corporate environmental performance? Empirical evidence from China - Johari, Jalila; Lin, Chen; Mohd Said, Ridzwana (Vilnius University Press, 2024)
Green funds, the backbone of promoting business transformation, have gradually become the focus of academic attention and discussion, but the existing literature has not provided systematic theoretical insights on whether green funds can promote Corporate Environmental Performance. To explore the relationship between green funds and Corporate Environmental Performance, based on the shareholder activism theory and the resource-based theory, using the panel data of Chinese A-share listed companies in Shanghai and Shenzhen from 2012 to 2021, and a two-stage Systematic Generalised Method of Moments (SYS-GMM), the impacts of Green Fund holdings, as well as Green Fund Characteristics on Corporate Environmental Performance, were analysed, the moderating effect of corporate reputation on the relationship between green funds and environmental performance was further examined. Results show that the shareholding ratio or volatility of green funds is significantly and positively related to Corporate Environmental Performance. The perspective based on the characteristics of green funds finds that the number, size, and age of green funds among the shareholders of listed companies positively affect Corporate Environmental Performance. Furthermore, corporate reputation significantly moderates the relationship between green funds and Corporate Environmental Performance. The conclusions obtained from this study not only enrich the literature in the field of institutional investors from the perspective of green funds but also provide essential insights into how capital markets can enhance the environmental effects of the real economy.